Cardiovascular Effects of Exercise in Young Hypertensives - Palatini, P. (International Journal of Sports Medicine, 2012)
Sedentary habits are largely responsible for the alarming rise in the prevalence of hypertension among young individuals. Regular aerobic exercise has been shown to reduce not only blood pressure (BP) in resting conditions but also BP reactivity to stressors. Much less is known about the long-term effects of physical activity on target organ damage in hypertension. Some studies have documented that exercise is able to decrease rather than increase left ventricular mass and that even competitive athletics have beneficial effects on the heart. In addition, physical activity during leisure has been found to be inversely associated with the progression of subclinical atherosclerosis and to delay aging dependent arterial stiffness. Isolated systolic hypertension in physically active young people is often an innocent clinical condition caused by an elevated pulse pressure amplification and low wave arterial reflection from peripheral sites, due to increased arterial elasticity. The above findings support a strategy of exercise training as an initial approach in the management of young sedentary patients in the early stages of hypertension. Caution should be used in subjects with more severe hypertension and every hypertensive athlete should be thoroughly investigated to exclude target organ damage and coronary artery disease.
Keywords: training; heart; carotid; sympathetic